PEGylated IL‐11 (BBT‐059): A Novel Radiation Countermeasure for Hematopoietic Acute Radiation Syndrome. Issue 1 (July 2018) - Kumar, Vidya P.; Biswas, Shukla; Sharma, Neel K.; Stone, Sasha; Fam, Christine M.; Cox, George N.; Ghosh, Sanchita P.
Abstract : Abstract: Interleukin-11 was developed to reduce chemotherapy-induced thrombocytopenia; however, its clinical use was limited by severe adverse effects in humans. PEGylated interleukin‐11 (BBT‐059), developed by Bolder Biotechnology, Inc., exhibited a longer half-life in rodents and induced longer-lasting increases in hematopoietic cells than interleukin‐11. A single dose of 1.2 mg kg −1 of BBT‐059, administered subcutaneously to CD2F1 mice (12–14 wk, male) was found to be safe in a 14 d toxicity study. The drug demonstrated its efficacy both as a prophylactic countermeasure and a mitigator in CD2F1 mice exposed to 60 Co gamma total-body irradiation. A single dose of 0.3 mg kg −1, administered either 24 h pre-, 4 h post-, or 24 h postirradiation increased the survival of mice to 70–100% from lethal doses of radiation. Preadministration (−24 h) of the drug conferred a significantly ( p < 0.05) higher survival compared to 24 h post-total-body irradiation. There was significantly accelerated recovery from radiation-induced peripheral blood neutropenia and thrombocytopenia in animals pretreated with BBT‐059. The drug also increased bone marrow cellularity and megakaryocytes and accelerated multilineage hematopoietic recovery. In addition, BBT‐059 inhibited the induction of radiation-induced hematopoietic biomarkers, thrombopoietin, erythropoietin, and Flt‐3 ligand. These results indicate that BBT‐059 is a promising radiation countermeasure, demonstrating its potential to be used both pre- and postirradiation for hematopoietic acute radiation syndrome with a broad window for medical management in a radiological or nuclear event. Abstract : Supplemental digital content is available in the text.